2014
DOI: 10.1095/biolreprod.113.113134
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization Affects Growth and Glucose Metabolism in a Sex-Specific Manner in an Outbred Mouse Model1

Abstract: The preimplantation period is a time of reprogramming that may be vulnerable to disruption. This question has wide clinical relevance since the number of children conceived by in vitro fertilization (IVF) is rising. To examine this question, outbred mice (CF1 × B6D2F1) conceived by IVF and cultured using Whitten medium and 20% O2 (IVFWM group, less optimal) or K simplex optimized medium with amino acids and 5% O2 (IVFKAA group, more optimal and similar to conditions used in human IVF) were studied postnatally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 53 publications
(74 reference statements)
9
119
2
1
Order By: Relevance
“…Yang and coworkers also found that cell death genes (BAX), antioxidant genes (MnSOD) and stress protective genes (HSP70) are elevated and apoptosis is increased in human embryos that were cultured at a 20% O 2 level . In addition, mouse embryos cultured in 20% O 2 showed pre-implantation epigenetic changes that altered metabolism later in life (Donjacour et al 2014). Specifically, male mice displayed glucose intolerance, heavier body weight and heart enlargement compared with in vivo fertilized embryos.…”
Section: Type Of Publication Referencesmentioning
confidence: 99%
“…Yang and coworkers also found that cell death genes (BAX), antioxidant genes (MnSOD) and stress protective genes (HSP70) are elevated and apoptosis is increased in human embryos that were cultured at a 20% O 2 level . In addition, mouse embryos cultured in 20% O 2 showed pre-implantation epigenetic changes that altered metabolism later in life (Donjacour et al 2014). Specifically, male mice displayed glucose intolerance, heavier body weight and heart enlargement compared with in vivo fertilized embryos.…”
Section: Type Of Publication Referencesmentioning
confidence: 99%
“…Donjacur et al have detected the distribution of body lean and fat mass in IVF offspring by dual energy X-ray absorptiometry (DEXA) scanning, and found that the fat mass exhibits an obvious increase as the extension of age [5]. Similarly, Tamashiro et al have reported that the mice derived from in vitro cultured embryos have many obesity-associated characteristics [21].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of imprinted genes has been observed on day 9.5 of the development after implantation of mouse embryos [3]. It has been reported that in vitro fertilization-embryo transfer (IVF-ET) manipulation was associated with low birth weight, Type-II diabetes, obesity, insulin resistance, [4,5]. However, the corresponding mechanisms leading to these issues are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fetal sex can affect milk yield in the existing lactation (Hinde et al, 2014) and it is conceivable that sex ratio of pregnancies in first lactation varied between groups. Given that culture system affected the nature of developmental programming in mice (Fernández-Gonzalez et al, 2004;Donjacour et al, 2014;, the effect of being born using a specific reproductive technology might depend on the particular details of the techniques employed. Accordingly, general conclusions should not be derived until the performance of animals derived from IVP or MOET is examined in a wide range of settings.…”
Section: Implications Of Bovine Datamentioning
confidence: 99%
“…In one experiment, addition of serum to the medium of embryos cultured from the one-cell to blastocyst stages resulted in offspring with altered behavioral responses in males and females, increased adult weight in females at 31 weeks of age and later and increased liver and heart size in both sexes at 20 month of age (Fernández-Gonzalez et al, 2004). Using in vitro fertilization and embryo culture, Donjacour et al (2014) evaluated effect of embryo culture medium on properties of the resultant offspring. Culture media evaluated were KSOM and Whitten medium.…”
mentioning
confidence: 99%